Parasites as biological tags in marine fisheries research: European Atlantic waters - MACKENZIE, K.; HEMMINGSEN, W. (Parasitology, 2015)
Studies of the use of parasites as biological tags for stock identification and to follow migrations of marine fish, mammals and invertebrates in European Atlantic waters are critically reviewed and evaluated. The region covered includes the North, Baltic, Barents and White Seas plus Icelandic waters, but excludes the Mediterranean and Black Seas. Each fish species or ecological group of species is treated separately. More parasite tag studies have been carried out on Atlantic herring Clupea harengus than on any other species, while cod Gadus morhua have also been the subject of many studies. Other species that have been the subjects of more than one study are: blue whiting Micromesistius poutassou, whiting Merlangius merlangus, haddock Melanogrammus aeglefinus, Norway pout Trisopterus esmarkii, horse mackerel Trachurus trachurus and mackerel Scomber scombrus. Other species are dealt with under the general headings redfishes, flatfish, tunas, anadromous fish, elasmobranchs, marine mammals and invertebrates. A final section highlights how parasites can be, and have been, misused as biological tags, and how this can be avoided. It also reviews recent developments in methodology and parasite genetics, considers the potential effects of climate change on the distributions of both hosts and parasites, and suggests host-parasite systems that should reward further research.